Specific Characteristics of Teaching Children to Picture Activity in Preschool Educational Organizations - Ashurova Tulganoy Ergashevna (Genius Publishing Group, 2022)
This article explores the problem of teaching preschoolers not only to be creative, but also to teach children to change subjects by introducing them to subjects
Keywords: attention, memory, thinking, models, patterns, visual activity, figurative, logical or abstract, independent and free